Rancang Bangun Mesin Pengaduk Adonan Kerupuk Semi Otomatis dan Penataan Manajemen untuk Meningkatkan Produktivitas UMKM Kerupuk Jaya Abadi, Sidoarjo - Ahmad Ajib Ridlwan; Suwito Djoko; Heru Arizal; Yunus (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The implementation of this PKM program aims to solve problems in the production and management aspects of cracker SMEs “UD. JAYA ABADI” owned by M. Subhan Abadi which is located in Tlasih village, Tulangan, Sidoarjo. The production capacity of these cracker SMEs is 400 kg/day. Types of crackers produced include fish crackers, onion crackers, and shrimp crackers. The priority problem in the production aspect of Mitra cracker SMEs is the low productivity (quality and quantity) of the production of mixing the cracker dough and the priority problem in the management aspect is that there is no bookkeeping of business financial flows. The process of mixing the raw material for crackers at the partner cracker SMEs is done manually by hand and trampled underfoot with a production capacity of 50 kg/hour. The solution to solving the priority problems in the production aspect is carried out through the design of the dough mixer machine for raw materials for crackers, semi-automatic, mechanical, electric motors and reducers and solutions to solving financial management problems are carried out through training activities and assistance in accounting for business financial flows using a simple cash book. The results achieved from the implementation of the PKM program are: (1) a semi-automatic mechanical mixer for crackers, an electric motor and a reducer with a production capacity of 500 kg/hour, and (2) the implementation of better financial management, which has been carried out in an orderly manner. business financial flows using a simple cash book.